Near Infrared Spectroscopy: A Rapid and Non-Destructive Technique to Assess the Ripeness of Oil Palm (Elaeis Guineensis Jacq.) Fresh Fruit. Issue 2 (April 2016) - Silalahi, Divo Dharma; Reaño, Consorcia E.; Lansigan, Felino P.; Panopio, Rolando G.; Bantayan, Nathaniel C.; Davrieux, Fabrice; Caliman, J.P.; Yuan, Yong Yit; Sudarno,
Near infrared (NIR) spectroscopy as a rapid and non-destructive technique was used with principal component analysis and linear discriminant analysis to develop an alternative technique for oil palm fresh fruit ripeness classification. The fruit samples were broadly classified into four main ripeness grades: unripe, under-ripe, ripe and over-ripe. A total of 3870 samples of individual fruits were taken at different stages of ripeness between 6 and 27 weeks after anthesis. Right after field collection, fresh samples were sent immediately to the laboratory for NIR and wet chemistry analysis. Two parameters, oil and moisture content in mesocarp were used as prior reference to determine the ripeness grades of oil palm fresh fruit. The NIR spectra of the ripe and over-ripe grades had higher absorbance compared to the unripe and under-ripe grades. The overall average accuracy of the classification by ripeness grades using this technique for both the training and the validation set samples was larger than 81%. In practical application, the rapid and non-destructive NIR technique has potential use for classifying oil palm fresh fruit into ripeness grades.